PENGARUH PEMBERIAN ULTRASOUND THERAPY DAN NEUROMUSCULAR TAPING DALAM MENINGKATAN AKTIVITAS FUNGSIONAL PADA KASUS OSTEOARTHRITIS LUTUT - Dewi, A.A.N, Trisna Narta; Pramana, Yudi; Utama, A.A.Gd, Eka Septian; P.Gd, Surya Adhitya (Sport and Fitness Journal, 2019)
Background: Osteoarthritis is a complaint characterized by abnormalities in the cartilage of joints and bones nearby, this complaint is commonly felt and has become a chronic joint disease. Cartilage abnormalities will result in bones rubbing against each other, resulting in symptoms of stiffness, pain and restriction of movement in the joints that will affect the quality of functional activities performed. The aim of this study was to determine the effect of ultrasound therapy and neuromuscular taping (nmt) in increasing functional activity in cases of knee osteoarthritis. Research method: The study used experimental with randomized design type pre test and post test control group design. The study was divided into 2 groups, namely group 1 would receive Ultrasound intervention and group 2 would receive Ultrasound and neuromuscular taping intervention. The number of samples in this study was 11 samples per group so that the total number of samples in the two groups was 22 respondents. Measurements of knee functional activity values were measured by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. Results: Group 1 with a value of p = 0,000 (p <0.05) which showed a significant difference between the value of tenderness before and after the intervention of ultrasound therapy. Group 2 obtained a value of p = 0,000 (p <0.05) indicating there was a significant difference between the value of tenderness before and after the intervention of ultrasound therapy and neuromuscular taping. The results of the calculation of the mean difference were p = 0,0001, the data showed that there was no difference in influence between groups, which means that the provision of ultrasound therapy and neuromuscular taping was no better in increasing functional activities of knee OA patients compared to ultrasound therapy. Conclusion: the provision of ultrasound therapy and neuromuscular taping is not better in increasing